Presidential Nomination in the Indonesian Legal System - Askar, Muhammad Afdhal (Jurnal Hukum Magnum Opus, 2024)
The background to writing this article was oligarchic practices in the Presidential Election process of the Republic of Indonesia. This writing aims to determine the causes of oligarchic practices and the importance of restructuring the presidential nomination process in the General Election in Indonesia. This research uses normative juridical research by testing positive legal norms with various theories and provisions for drafting laws. From this research, it is known that the practice of orligarchy occurs because the requirement for presidential nominations must be through a political party, while the internal processes of political parties are often not transparent because decisions are often made only by elite groups or the general chairman. This is not in accordance with the spirit of deliberation and popular sovereignty as stated in the 4th Principle of Pancasila and UUD NRI 1945. Therefore, the provisions of Article 222 of Law No.7/2017 which contain provisions for presidential nomination must be made more stringent by including provisions for the nomination process that more transparent through opportunities for access and evaluation of the community as voters.